Development of Interactive Learning Media Crossword Puzzle Integrated Virtual Laboratory in Science Learning Vibrations and Waves Material - Tirtawaty Abdjul; Muhammad Yusuf; Nurhayati (Jurnal Penelitian Pendidikan IPA, 2024)
Learning media is an essential component in supporting learning objectives. Teachers are expected to make optimal use of these media. This research aims to develop interactive learning media through crossword puzzles integrated with virtual laboratories that are valid, practical, and effective. This research is included in the type of development research that refers to the ADDIE model Research and Development Model: Analysis, Design, Development, Implementation, and Evaluation. The tools used in this research are the validation sheet, learning process implementation observation sheet, student response questionnaire, student activity observation sheet, and learning outcomes test. The research results show that the interactive crossword puzzle integrated virtual laboratory learning media is categorized as valid, practical, and effective because the combination of learning and games provides a deep and enjoyable learning experience for users. Meanwhile, the virtual laboratory allows experiments to be conducted virtually so that they can be accessed anytime and anywhere.